Oxidative Stress Renders Retinal Pigment Epithelial Cells Susceptible to Complement-mediated Injury - Thurman, Joshua M. (American Society for Biochemistry and Molecular Biology, 2009)
Uncontrolled activation of the alternative pathway of complement is thought to be associated with age-related macular degeneration (AMD). The alternative pathway is continuously activated in the fluid phase, and tissue surfaces require continuous complement inhibition to prevent spontaneous autologous tissue injury. Here, we examined the effects of oxidative stress on the ability of immortalized human retinal pigment epithelial cells (ARPE-19) to regulate complement activation on their cell surface. Combined treatment with H(2)O(2) (to induce oxidative stress) and complement-sufficient serum was found to disrupt the barrier function of stable ARPE-19 monolayers as determined by transepithelial resistance (TER) measurements. Neither treatment alone had any effect. TER reduction was correlated with increased cell surface deposition of C3, and could be prevented by using C7-depleted serum, an essential component of the terminal complement pathway. Treatment with H(2)O(2) reduced surface expression of the complement inhibitors DAF, CD55, and CD59, and impaired regulation at the cell surface by factor H present within the serum. Combined treatment of the monolayers with H(2)O(2) and serum elicited polarized secretion of vascular epidermal growth factor (VEGF). Both, secretion of VEGF and TER reduction could be attenuated using either an alternative pathway inhibitor or by blocking VEGF receptor-1/2 signaling. Regarded together, these studies demonstrate that oxidative stress reduces regulation of complement on the surface of ARPE-19 cells, increasing complement activation. This sublytic activation results in VEGF release, which mediates disruption of the cell monolayer. These findings link oxidative stress, complement activation, and apical VEGF release, which have all been associated with the pathogenesis of AMD.